PENGARUH CONTENT MARKETING TIKTOK AFFILIATE DAN LIVE STREAMING TERHADAP KEPUTUSAN PEMBELIAN PRODUK FASHION PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI IKIP PGRI BOJONEGORO - rozita, findameila; fradani, ayiscrusma; Kholiqul Amin, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the current era of globalization, competition across various sectors—political, technological, and economic—has become increasingly intense. In the economic sector, for instance, Indonesia has witnessed the emergence of numerous new businesses as a consequence of economic growth driven by globalization. The entry of new business players naturally intensifies competition. As more businesses operate within the same sector, consumers are presented with more choices to meet their needs and expectations. However, many marketers have yet to fully understand the impact of content marketing, TikTok affiliate programs, and live streaming on fashion product sales. This study aims to examine the influence of TikTok Affiliate Content Marketing and Live Streaming on purchasing decisions for fashion products among students of the Economic Education Study Program at IKIP PGRI Bojonegoro. This research employs a quantitative method. The sampling technique used is purposive sampling combined with the Slovin formula, resulting in a sample size of 73 respondents. Data was collected through the distribution of questionnaires measured using a Likert scale. Data analysis was conducted using SPSS version 26.0. The results of this study indicate that TikTok Affiliate Content Marketing and TikTok Live Streaming jointly have a significant influence on the purchasing decisions of fashion products by students at IKIP PGRI Bojonegoro.